Metoda Przemieszczeń dla Układów Lepkosprężystych - J. Kubik (Engineering Transactions, 1971)
In the paper the equations of the method of displacements are given for visco-elastic systems and their properties are analyzed. The more significant of the analyzed properties of the set of equations of the method of displacements arc the harmonicity and of displacement states and stresses of the system caused by harmonic forcing and the cases of identical displacement states in elastic and visco-elastic systems.